UI/UX Design of a Web-Based Linmas Attendance System in Desa Abiansemal Using Design Thinking Methods Based on Face Recognition and Geolocation - Putu Yoka Angga Prawira; I Putu Yoga Indrawan (Jurnal Krisnadana, 2026)
Currently, the management of village security forces (Linmas) in Desa Abiansemal uses manual attendance system which is vulnerable to location spoofing and buddy punching. The purpose of this research is to design and implement a Web-Based Linmas Attendance System as an effort in improving accuracy and discipline of Administrative. The implemented solution combines Geofencing technologies, applied through validation of GPS coordinates based on the Haversine formula and AI based Facial Recognition done using face-api. js for real-time biometric authentication. The system is built on the Laravel framework with a MySQL database. We performed functionality testing as well as the SUS (System Usability Scale) method to evaluate the interface and user experience. The results show that the technology effectively prevents ghosting by verifying not only the attendance of a user within the determined duty radius but also visually confirming the identity of a dutiable person. A quantitative evaluation scored an SUS score of 77.5 within a range to the "Good" rating category for interface usability. The finding of the study indicates that the prototype meets user expected in terms of effectiveness and comfort making it a robust and viable digital solution for contemporary village governance.